2011
DOI: 10.1016/j.medin.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Utilización de la ventilación mecánica no invasiva en neumonía grave por virus H1N1

Abstract: Based on our results, increased use of noninvasive mechanical ventilation in future epidemics coujld be proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 19 publications
0
10
2
4
Order By: Relevance
“…Whether NIV delivered by helmet could reduce the intubation rate and mortality was still causing controversy [15, 16], furthermore, the effect on gas exchange was also confusing. Some studies indicated NIV delivered by helmet could improve oxygenation further compared with a face mask [17, 18], while others showed there was no significant difference in oxygenation [19–21], and some studies even demonstrated helmet-induced carbon dioxide rebreathing [22]. …”
Section: Introductionmentioning
confidence: 99%
“…Whether NIV delivered by helmet could reduce the intubation rate and mortality was still causing controversy [15, 16], furthermore, the effect on gas exchange was also confusing. Some studies indicated NIV delivered by helmet could improve oxygenation further compared with a face mask [17, 18], while others showed there was no significant difference in oxygenation [19–21], and some studies even demonstrated helmet-induced carbon dioxide rebreathing [22]. …”
Section: Introductionmentioning
confidence: 99%
“…A retrospective observational study evaluated the use of NIV in all patients admitted to intensive care with presumed or confirmed influenza A (H1N1) infection and hypoxemic acute respiratory failure [49]. NIV was delivered as CPAP and PSV with a helmet or face mask.…”
Section: Resultsmentioning
confidence: 99%
“…The helmet presented similar oxygenation rates in eight [29,41,42,49,54,57-59] and similar intubation rates in four [32,42,57,59] of these compared to the face mask. The outcome was similar in six studies [32,42,54,57-59].…”
Section: Discussionmentioning
confidence: 99%
“…2 GTEI informative bulletin of the SEMICYUC reported that 80.3% (n = 237) of the patients required MV. 18 However, of the patients included in the registry of Belenguer et al 19 with P0 2 /Fi0 2 at admission, 87 presented parameters indicative of a good prognosis in the first hour, as defined in the literature. These subjects posteriorly required intubation [.…”
mentioning
confidence: 98%